Synthesis of Fe-doped alumina transparent ceramics by co-precipitation and vacuum sintering. Issue 1 (January 2018) - Huang, Jinshan; Liao, Qilong; Wang, Fu; Huang, Xu; Zhu, Hanzhen
Abstract: In this paper Fe-doped alumina (Al2 O3 ) transparent ceramics were successfully synthesized by a co-precipitation method and sintering under vacuum. The effect of Fe doping on the microstructure and transmittance of the as-prepared Al2 O3 ceramics was investigated in detail. Initially, Fe-doped Al2 O3 precursors were synthesized by a co-precipitation method using polyethylene glycol (PEG2000) and (NH4 )2 SO4 as dispersant and NH4 HCO3 as precipitant. Subsequently, Fe-doped Al2 O3 nanopowders were prepared by heat-treating the precursors at 1200 °C for 2 h. Finally, Fe-doped Al2 O3 ceramics were obtained by pre-heating the Fe-doped Al2 O3 pellets at 600 °C for 2 h and sintering at 1750 °C for 8 h under vacuum, using the Fe-doped Al2 O3 powders as raw material. The results show that doping by a small amount of Fe (≤ 0.15 wt%) improves the light transmittance of Al2 O3 ceramics. However, excessive Fe-doping leads to an increase of pores within Al2 O3 grains, resulting in the reduced transmittance of the final Al2 O3 ceramics. The obtained 0.15 wt% Fe-doped Al2 O3 ceramic shows total light transmittance of > 80% in the wavelength range of 300–800 nm.